2022
DOI: 10.3390/ijerph19169872
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rheumatic Heart Disease Mortality in the Chinese Population: A JoinPoint and Age–Period–Cohort Study

Abstract: (1) Background: We aimed to analyze rheumatic heart disease (RHD) mortality trends in China’s urban and rural areas and to determine the roles of age, period, and cohort effects. (2) Methods: Based on mortality data extracted from the China Health Statistics Yearbook, we calculated the crude mortality rate of RHD. Age–adjusted rates were computed by the direct method using the 2020 census as the standard population. The annual percentage change (APC) and average annual percentage change (AAPC) were determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…After segmentation, the researchers can clearly see the change trend and then analyze the background and causes of the segment points. In recent years, JPR has been increasingly used by researchers to determine the trend of tumors, COVID‐19, AIDS, smoking, and other diseases 14–17 . Further, the cluster analysis used in the above literatures (such as hotspot analysis and spatial correlation analysis) give more insights into the spatial distribution characteristics of HFRS, 10,11 but ignore its temporal evolution pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After segmentation, the researchers can clearly see the change trend and then analyze the background and causes of the segment points. In recent years, JPR has been increasingly used by researchers to determine the trend of tumors, COVID‐19, AIDS, smoking, and other diseases 14–17 . Further, the cluster analysis used in the above literatures (such as hotspot analysis and spatial correlation analysis) give more insights into the spatial distribution characteristics of HFRS, 10,11 but ignore its temporal evolution pattern.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, JPR has been increasingly used by researchers to determine the trend of tumors, COVID-19, AIDS, smoking, and other diseases. [14][15][16][17] Further, the cluster analysis used in the above literatures (such as hotspot analysis and spatial correlation analysis) give more insights into the spatial distribution characteristics of HFRS, 10,11 but ignore its temporal evolution pattern. To this end, wavelet cluster analysis provides an efficient tool to character the internal variation of HFRS in a space−time−frequency domain together with the series from various spatial locations.…”
mentioning
confidence: 99%
“…In China, the risk of ARF and RHD is medium to high ( 26 ). The incidence of ARF and RHD had peaked in the 1940s–1950s, but began to decline during the 1950s–1970s ( 26 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, there was no difference in mortality between males and females. Similarly, while some studies have shown that females had a higher risk of mortality than males, 37 others 1,8 reported the opposite. Indeed, in our previous review, we concluded that it is not clear whether sex plays a role in the diagnosis, management and prognosis of MS and hence a need for research to explore the mechanisms for the differences 17 .…”
Section: Discussionmentioning
confidence: 95%